Reducing free fatty acids and peroxide value in used cooking oil using activated coconut shell charcoal combined with lemongrass stems - Nurlaila Agustikawati; Rizky Nugrahani; Fitri Setianingsih (Jurnal Pijar Mipa, 2023)
Used cooking oil is obtained from the residue of the frying process, which has been used repeatedly where the fatty acids are increasingly saturated and the triglyceride content breaks down into volatile and non-volatile components that dissolve in oil. Used cooking oil waste can cause an increase in COD and BOD levels in waters, resulting in the death of aquatic biota. The aims of this study were (1) to determine the optimum contact time of activated charcoal d combination of citronella sticks on decreasing levels of free fatty acids, (2) to determine the optimum contact time of activated charcoal d combination of citronella sticks on decreasing peroxide numbers, (3) to determine the average percentage of free fatty acid reduction and peroxide value in the clarification of used cooking oil using activated coconut shell charcoal combined with lemongrass stems. This research method is a laboratory experiment with despising, neutralization, and bleaching stages. The results showed that the average decrease in optimum free fatty acid levels occurred at 60 minutes of contact time, namely A3 at 73.86%, B3 at 66.67%, and C3 at 82.74%. The average decrease in the optimum peroxide number occurred at a contact time of 60 minutes, namely A3 of 57.16%, B3 of 52.85%, and C3 of 49.68%. So, the coconut shell-activated charcoal combined with lemongrass stems effectively clarifies the used cooking oil. In the future, it is necessary to vary the absorbent particle size to improve the quality of the waste cooking oil so that it can be reused.